Five Albanian Villages Guidelines for a Sustainable Tourism Development through the Enhancement of the Cultural Heritage - Laurìa, Antonio (Studi e saggi, 2020)
This book is the result of a research project designed and carried out at the Department of Architecture, University of Florence. This research was based on the transfer of knowledge from members of the Albanian Diaspora in Italy (university students, young architects and researchers) to their home country. This unique process blazed a trail in the Albania-related studies by creating a methodology, which could be replicated not only in Albanian rural contexts, but also elsewhere. The book constitutes a structured tool for generating sustainable and socially inclusive territorial development processes in five lesser-known Albanian cultural sites. Their tangible and intangible cultural heritage was seen as a driving factor for triggering development processes aimed at improving the inhabitants' quality of life and strengthening local identity and social networks. Through concrete proposals and strategies, the book offers scenarios and solutions capable of enhancing the potential of each village and, at the same time, counteracting the effects of land abandonment that so often characterise them.